ICATFORLEARNING as Interpreting Media:Does It Fulfill the Students' Need? - Atsani Wulansari; Gilang Fadhilia Arvianti; Agnira Rekha (Universitas Pendidikan Indonesia, 2022)
Teaching interpreting using technology is necessitated, moreover, in this online learning era. Lecturers in interpreting classes should train their students with interpreting skills and technology to increase their proficiency level. Likewise, Introducing the students with interpreting technology is also substantial as their expertise in the language industry in the future. Thus, icatforlearning was developed as one of the media to teach interpreting. However, a myriad question about this website as teaching media still arises. This research tries to explore the students' view about icatforlearning as media in interpreting class. It will be the initial data that is beneficial to develop the website. A descriptive qualitative method in the form of a case study was applied in this study. The researchers used questionnaire and interview to collect the data. The result shows that change and development in some parts and functions in icatforlearning are required to fulfill the students' need in practicing consecutive and simultaneous interpreting.